AKTIVITAS INHIBISI LIMA BELAS JENIS MUTU TEH HITAM ORTODOKS (CAMELLIA SINENSIS VAR. ASSAMICA) PADA ?-AMILASE - Tunisha, Sofia
Diabetes mellitus is a metabolic disorder of carbohydrate, fat and protein with characteristics of hyperglycemia (blood sugar levels higher than normal). One of the enzymes involved in carbohydrate digestion process is ?-amylase. ?-amylase breaks down polysaccharides into dextrine. ?-amylase inhibitory activity can reduce blood sugar levels so that it has potential for treatment of diabetes. Tea (Camellia sinensis) is a plant known to have ?-amylase inhibitory activity but the activity has not been studied for fifteen grades of orthodox black tea. This study aims to determine the ?-amylase inhibitory activity of fifteen grades of orthodox black tea. Extraction performed by the method based on the use of traditional people. ?-amylase inhibitory activity was measured using the ratio of reducing sugar formed from the reaction between the enzyme and the substrate with a reducing sugar which is formed from the reaction of the enzyme, substrate and extracts. Formed reducing sugar is reacted with 3,5-dinitrosalisilat acid, then the product of the reaction is measured using a spectrophotometry UV-visible at ?540 nm. Acarbose as a positive comparison was tested in a concentration of 200 ppm. ?-amylase inhibitory activity expressed as a percent inhibition. Percent inhibition of ?-amylase from fifteen grades of orthodox black tea, are PF III (93.93 ± 0.32%), Dust (93.43 ± 0.54%), BM (91.81 ± 0.67%) , Dust II (90.36 ± 1.16%), PF I (86.4 ± 1.98%), BP (85.35 ± 4.21%), Dust III (85.3 ± 2.49% ), B0PF (83.93 ± 1.82%), BT (83.93 ± 2.45%), BOP (83.75 ± 2.39%), BTL (85.35 ± 4.21%), PF II (79.83 ± 5.84%), BT II (78.63 ± 3.45%), BP II (76.92 ± 3.61%), BBL (65.43 ± 4.12%) . The tea grade that has the highest percent inhibition of ?-amylase is PF III (93.93 ± 0.32%).